The Effect of Workforce Formation and Skills on Employee Performance Through Motivation as an Intervening Variable at PT PLN (Persero) UP2D North Sumatera - Doli Panca Setiawan; Husni Muharram Ritonga; Hernawaty (CV. Doki Course and Training, 2026)
The purpose of this research is to analyze how the creation of the workforce and their competencies impact the effectiveness of employees, considering motivation as an intermediary element within PT PLN (Persero) UP2D North Sumatra. Employing a quantitative research design, information was gathered through surveys distributed among 117 staff members. The method used to analyze the information was Partial Least Squares-Structural Equation Modeling (PLS-SEM). The discovery reveals that the development of the workforce and the skills possessed have a favorable and notable influence on how employees perform. Additionally, the study demonstrated that both factors also exert a favorable and substantial influence on workplace motivation. Workplace motivation independently demonstrates a favorable and considerable effect on employee effectiveness. Nonetheless, the examination of the secondary influence suggests that motivation does not act as a mediator in the connection between the creation of the workforce and competencies alongside employee performance. In conclusion, enhancements in employee performance are more immediately impacted by the composition of the workforce and the skills they bring. The results of this investigation are anticipated to supply administration with factors to consider when attempting to increase employee effectiveness by managing the formation of the workforce and advancing skill sets.